KARAKTERISTIK ASAP CAIR TEMPURUNG NYAMPLUNG - Santiyo Wibowo (Jurnal Penelitian Hasil Hutan, 2012)
Smoke liquid can be used as a food preservative. One of material used to produce smoke liquid is nyamplung shell waste that is still unused yet. The purpose of this experiment was to look at the effect of pyrolysis temperature and duration of pyrolysis time to physico chemical properties of smoke liquid from nyamplung shell. Smoke liquid processing to be arranged at pirolysis temperature level of 200°C, 300°C, 400C, 500 C and time of processing 5 hours and 7 hours. The results showed that the highest quality of smoke liquid obtained at condition of temperature 500 C. and 5 hours i.e: yield 45,3%, density 1,009 g/ml, fenol value 3,95%, and acid value 9,47%.